2019
DOI: 10.7150/jca.29457
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA UASR1 promotes proliferation and migration of breast cancer cells through the AKT/mTOR pathway

Abstract: Long non-coding RNAs (lncRNAs) are non-coding RNAs longer than 200 nucleotides that function as regulatory factors in many human diseases, including cancer. However, majority of lncRNAs remain to be characterized. In this study, we characterized a novel lncRNA transcript, named UNC5B antisense RNA1 (UASR1). UASR1 is 647bp in length consisting of two exons. This lncRNA is an antisense of intron 1 of unc-5 netrin receptor B (UNC5B) gene. In breast cancer tissues, UASR1 was upregulated. Ectopic expression of UASR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…[ 24 25 26 ] For example, UASR1 has a high expression in BC tissues and promotes cancer cell growth, proliferation, wound healing and migration through the AKT/mTOR signaling pathway. [27] MALAT1 is considered an oncogenic regulator of BC, which accelerates angiogenesis through miR-145 in MCF-7 cells to enhance aggressiveness of BC. [28] Its worth noting that some lncRNAs have been regarded as potential prognosis markers for BC, according to the previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 25 26 ] For example, UASR1 has a high expression in BC tissues and promotes cancer cell growth, proliferation, wound healing and migration through the AKT/mTOR signaling pathway. [27] MALAT1 is considered an oncogenic regulator of BC, which accelerates angiogenesis through miR-145 in MCF-7 cells to enhance aggressiveness of BC. [28] Its worth noting that some lncRNAs have been regarded as potential prognosis markers for BC, according to the previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…The functionality of UASR1 has only been investigated in breast cancer ( 13 ). It was observed that UASR1 was upregulated in breast cancer and that it interacted with the AKT/mTOR pathway to promote the migration and proliferation of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functions of most lncRNAs remain elusive. lncRNA UASR1 (UASR1) has been characterized as an oncogenic lncRNA in breast cancer ( 13 ). In a recent study, UASR1 was reported to promote the proliferation of CRC cells by interacting with the mTOR pathway ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there are only several literatures correlated with UNC5B-AS1 in cancers can be searched. These studies reveal that UNC5B-AS1 is upregulated and relevant to proliferation, migration and invasion in ovarian cancer, breast cancer, thyroid cancer and colon cancer [28][29][30][31]. However, there have no reports of UNC5B-AS1 in GBM.…”
Section: Discussionmentioning
confidence: 99%